Monkeying around Anthropocene: Patterns of human-nonhuman primates’ interactions in Brazil - Nunes, Vitoria Fernandes; Macedo Lopes, Priscila; Gonçalves Ferreira, Renata (Ethnobiology and Conservation, 2021)
In Anthropocene, approximately 70% of all terrestrial ecosystems are highly modified by human activities and more than a half of all primate’s species in the world are endangered. Here we present results of a systematic review on published articles with an Ethnoprimatology approach, aiming to assess the nationwide pattern and quality of proximity/interaction between human-nonhuman primates in Brazil, a country vulnerable to high deforestation rates while having the highest primate biodiversity in the world. The first article was published 29 years ago and add up to only 36 published articles until present time. Most studies were conducted in Atlantic forest, but higher number and diversity of interactions was described for Amazon. Sapajus, being a generalist and semi-terrestrial primate, was the most cited genus and had the greatest diversity of interactions, including garbage foraging and crop-raiding. Alouatta, the second most cite one, had more symbolic/mystic relationships. Some specialized or forest-specific primates are scarcely mentioned. Studies carried out in both rural and urban environment are almost equal in number but showed differences in types of interactions they describe: garbage foraging, crop-raiding by primates and food offering by humans happening in more urbanized areas and symbolic/mystic relationships and beliefs around nonhuman primates described in rural/indigenous settlements. We urge future studies to describe interactions and proximity carefully specifying the context where they occur. It is relevant to maintain the growing curve of Ethnoprimatological studies in Brazil as a way to aggregate information about different populations of species and help to base conservation strategies of co-existence.